DESCRIPTION BEHAVIOR DOCTOR AND NURSE ABOUT PREVENTION TRANSMISSION OF TB DISEASE - Indah Sahana; Zarfiardy Aksa Fauzi; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTDoctor and nurse have a high risk for contracting TB because often dealing directly with patients. Data in Africa Country (84%) health workers infected TB. Data estimated Malaysia about incidence of TB among health workers has also risen in 2008 (80.59%), 2009 (71.42%) and 2010 (97.86%). Prevention can be done if they have good knowledge, attitude and practice about prevention of TB transmission. The Purpose of this study was to be describe behavior doctor and nurse about prevention transmition TB disease. This research was held in twenty primary health Pekanbaru Citty by using descriptive method with cross sectional approach. Samples in this study were doctor and nurse in primary health Pekanbaru. The samples consisted of 128 respondents. The respondents in this study aged 35-45 years at most that doctors (50.0%) and nurses (51.6%), the majority of which are female doctors (95.8%) and nurses (97.5%), educated bachelor degree doctor (100%) and diploma 3 in nurse (67 %). The results of this study, the levelof knowledge in the category of good, that doctors (97.9%) and nurses (97.5%), while a positive attitude in the category of physician (85.4%) and nurses (82.5%), while the action obtained in the category enough that a doctor (100%) and nurses(100%).Keywords: Knowledge, attitudes, practice, behaviors, prevention of TB transmission